Measurement of Thermal Neutron Capture Cross Section and Resonance Integral for the \(^{45}\)Sc\((n,γ)^{46}\)Sc Reaction with Pulsed Neutrons - Do, Nguyen Van; Khue, Pham Duc; Thanh, Kim Tien; Hien, Nguyen Thi; Guinyun, Kim (Communications in Physics, 2014)
Thermal neutron capture cross section and resonance integral for the $^{45}$Sc(n,$γ )^{46}$Sc reaction were measured by the activation method using the $^{197}$Au(n,$γ )^{198}$Au reaction as a single comparator. The high-purity scandium and gold samples with and without Cd cover with the thickness of 0.5 mm were irradiated in a pulsed neutron field of the 100 MeV electron linac of the Pohang Accelerator Laboratory (PAL). The induced activities in the activated foils were measured with a well calibrated HPGe detector. In order to improve the accuracy of the experimental results the effect of the non-ideal epithermal spectrum was taken in to account by determining the neutron spectrum shape factor ($α )$, and the corrections for the thermal (G$_{th})$ and the resonance (G$_{epi})$ neutron self-shielding effects, the $γ $-ray attenuation (F$_{g})$ and the $γ $-ray coincidence summing effect were made. The thermal neutron cross-section for the $^{45}$Sc(n,$γ )^{46}$Sc reaction has been determined to be $σ _{o}$ = 27.6 $± $ 0.8 barn. By assuming the cadmium cut-off energy of 0.55 eV, the resonance integral for the $^{45}$Sc(n,$γ )^{46}$Sc reaction has been determined to be I$_{o}$ = 12.7 $± $ 0.7 bar. The present results are compared with the reference data and discussed.